Mathematical Resilience as a Predictor of Academic Burnout Among Prospective Mathematics Teachers: Evidence from Partial Least Squares Structural Equation Modeling - widyawati, Santi; Rosyidah, Ummi; Iskandar, Iskandar; Nurra, Reva Aisyah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Academic burnout has become an increasingly prevalent issue among prospective mathematics teachers due to escalating academic demands, intensive coursework, and persistent performance expectations. Within the framework of the Job Demands–Resources Theory, mathematical resilience is considered an important personal resource that may help students cope with academic challenges and reduce burnout. This study aimed to examine the effect of mathematical resilience on academic burnout among prospective mathematics teachers. A quantitative explanatory survey with a cross-sectional design was employed involving all 57 undergraduate students enrolled in the Mathematics Education Program through a census sampling technique. Data were collected using validated self-report questionnaires measuring mathematical resilience and academic burnout. The proposed structural model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model demonstrated satisfactory psychometric properties, including adequate indicator reliability, convergent validity, discriminant validity, and internal consistency reliability. The structural model revealed that mathematical resilience had a significant negative effect on academic burnout (β = −0.834, t = 11.223, p < 0.001), explaining 69.6% of the variance in academic burnout (R² = 0.696). These findings indicate that students with higher levels of mathematical resilience are less likely to experience academic burnout despite demanding academic environments. The study extends the application of the Job Demands–Resources Theory in mathematics teacher education by highlighting mathematical resilience as a key protective factor for students' psychological well-being. The findings also provide practical implications for designing resilience-based educational interventions to promote healthier and more sustainable learning experiences